Welding Automation Design using Metal Inert Gas for Straight and Circular Welding - Suwandi Marwoto; Dwi Saputro, Danang; Karnowo, Karnowo; Maulana, Sonika (Rekayasa, 2024)
An automatic welding machine is a tool used to carry out welding semi-automatically. The welding process is carried out using an Arduino as a microcontroller and a TB6560 driver as a Nema 23 stepper motor driver. Operation of the tool is carried out using Candle software. The tool movement system uses a lead screw and nut block on the Z axis as well as a timing belt and timing pulley to drive the X and Y axes. This machine has dimensions of 1200 mm long, 800 mm wide and 1250 mm high. The research model used is RnD. Tool testing is carried out by giving movement commands in the form of straight lines and circles to determine the accuracy of the movement, then testing is carried out using a welding machine to determine the welding results. Testing was carried out with variations of straight lines with variations of 18 mm, 24 mm, 25 mm, 30 mm, 36 mm, 42 mm, 50 mm, 75 mm, 100 mm, 125 mm and circle variations of 50 mm, 75 mm and 100 mm. Each variation was tested 3 times to produce an average backlash of 0.250 mm. Automatic welding machine can produce neat and even welds on straight welding, but there are still shortcomings in the results of circular and square welding. Adjustment of welding parameters and settings on the welding machine used needs to be done to improve the quality of the weld results.